Frequency and Risk Factors of Meconium Aspiration Syndrome in Babies Delivered to Mothers with Meconium Stained Amniotic Fluid - Tanveer, Sidra; Basheer, Faisal; Khushdil, Arshad; Motlaq, Fady MA; Nawaz, Raazia; Javed, Maria (Pakistan Armed Forces Medical Journal, 2022)
ObjectiveTo determine the frequency and risk factors of meconium aspiration syndrome in babies delivered to mothers with meconium stained amniotic fluid attending neonatal unit of tertiary care hospital. Study designProspective cross sectional study Place and duration of studyNeonatal Unit “Pak Emirates Military Hospital”, Rawalpindi from 1st January to 30th September 2018Patients and methodsAll pregnant women with cephalic presentations with either spontaneous vaginal delivery (SVD) or lower segment cesarian section (LSCS) mode of delivery and having light-yellow to thick dark-green color liquor after spontaneous or artificial rupture of membrane were enrolled. Meconium aspiration syndrome along with risk factors like gestational age, weight, gender, mode of delivery, grades of meconium, and mortality was noted. ResultsOf 384 patients, meconium aspiration syndrome was observed in 37 (9.6%) patients. Meconium aspiration syndrome was 2.97 times higher among patients with >36 weeks of gestation (AOR: 2.97, 95% CI: 1.12-7.89), 61% higher among patients with ≤3 kg weight (AOR: 0.39, 95% CI: 0.19-0.85), 89% higher among females (AOR: 1.89, 95% CI: 0.91-3.95), 83% higher among patients with SVD (AOR: 1.83, 95% CI: 0.89-3.75), 4.12 times higher among patients with grade III (AOR: 4.12, 95% CI: 0.51-33.45) and 8.65 times higher among patients with grade II color liquor (AOR: 8.65, 95% CI: 1.11-67.45). ConclusionMeconium aspiration syndrome frequency was found considerably higher. In particular, newborn having higher gestational age, increased weight, female gender, SVD as the mode of delivery, grade III and grade II meconium were reported as the significant risk-factors.